“É onde a família geralmente busca socorro”: a Atenção Primária à Saúde e o Cuidado Paliativo - BARROS, Gabriela Cirqueira De Souza (2021)
Introduction: Palliative Care (PC) is an approach to patients and families who face lifethreatening diseases or those in the final stages of life. About 60 to 70% of individuals with progressive and advanced disease can be cared for in Primary Health Care (PHC). The family doctor must be able to meet this demand, promoting care with comprehensive responses, respecting the person's autonomy and values. Objective: To understand the perception of physicians about PC performed in PHC. Methodology: Qualitative study, carried out with physicians working in the Family Health Strategy (ESF), in the city of São Luís – MA, in 2020. The subjects were included by progressive inclusion, finalized by the saturation criterion. Data collection took place after signing the Free and Informed Consent, at the Basic Health Unit, through an open interview, which was recorded and transcribed for further analysis. Data analysis was performed using Content Analysis, in the Thematic Analysis modality. This project was approved by the Ethics Committee of the Hospital Universitário Presidente Dutra, through protocol 30760320.9.0000.5086. Results: Data analysis generated three categories: “We feel that it is limited”: what does Palliative Care mean; “Because we're just a drop”: facilities and difficulties to perform CP in PHC; “Primary Care has a way, because it is complete?”: performing PC in PHC. Conclusion: PHC has important characteristics that facilitate the performance of PC by its professionals, such as longitudinally and proximity to the community. Thus, it is the place of search for families and patients who need professional support at all stages of life. Despite the factors that make it difficult to perform PC in PHC, the doctors interviewed believe it is possible to apply this care to patients and families who demand it in the primary sphere. For this, it is necessary to invest the State in health and intersectoral, better integration to the Health Care Network (RAS), training and valuing professionals, reducing the workload, in addition to encouraging dialogue and awareness of professionals and the population about the theme.